2021
DOI: 10.1016/j.celrep.2021.109414
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive features of SARS-CoV-2-specific T cells predict recovery from severe COVID-19

Abstract: Although T cells are likely players in SARS-CoV-2 immunity, little is known about the phenotypic features of SARS-CoV-2-specific T cells associated with recovery from severe COVID-19. We analyze T cells from 34 COVID-19 patients with severities ranging from mild (outpatient) to critical culminating in death. Relative to patients that succumbed, individuals that recovered from severe COVID-19 harbor elevated and increasing numbers of SARS-CoV-2-specific T cells capable of homeostatic proliferation. In contrast,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 71 publications
7
78
0
Order By: Relevance
“…PET/CT imaging showed regions of ground glass opacity and consolidation with elevated 18 FDG uptake in the lungs on day 3 after SARS-CoV-2 infection, which completely resolved by day 9. A longitudinal scRNAseq analysis identified early type I IFN responsive monocyte, macrophage, and dendritic cells in PBMC and BAL that mostly dissipated prior to the arrival of virus-specific CD8 and CD4 T cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…PET/CT imaging showed regions of ground glass opacity and consolidation with elevated 18 FDG uptake in the lungs on day 3 after SARS-CoV-2 infection, which completely resolved by day 9. A longitudinal scRNAseq analysis identified early type I IFN responsive monocyte, macrophage, and dendritic cells in PBMC and BAL that mostly dissipated prior to the arrival of virus-specific CD8 and CD4 T cells.…”
Section: Discussionmentioning
confidence: 98%
“…), for a total dose of 2x10 6 TCID50 (Table 1). 18 FDG PET/CT imaging showed evidence of heterogeneous inflammatory foci with increased 18 FDG uptake (Fig 1A , B) and lesion density (Fig 1A, C) in the lungs of 5 of 6 animals at day 3 post-infection, which resolved by day 9. Total genomic Nucleocapsid (gN) and subgenomic Nucleocapsid (sgN) RNA levels from nasal and throat swabs peaked 1 to 2 days post-infection and decreased to undetectable levels by day 7 to 10 (Fig 1D).…”
Section: Radiologic and Virological Outcomes Of Sars-cov-2 Infection In Rhesus Macaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic HIV-infected individuals, IL-7Ra expression was significantly lower than in HAART-treated and healthy controls, suggesting the expansion of CD127 negative T cells in chronic viral infection (31). CyTOF analysis revealed that lower levels of IL-7Ra (CD127) were identified in severe COVID-19 patients compared to mild cases (32); patients who survived from severe SARS-CoV-2 illness showed elevated expression of IL-7Ra (CD127) compared to nonsurvivors (32). Thus, further studies are warranted to understand the relation between IL-7Ra (CD127) expression and plasma/serum levels of IL-7 in COVID-19 patients.…”
Section: Elevated Il-7 In Sars-cov-2 Infectionmentioning
confidence: 96%
“…In addition to comorbidities, COVID-19 also exhibits sex biases, with male patients being more susceptible to developing severe disease; hence future studies evaluating RBD-mAb therapy in male animals would be informative. Second, other factors, such as innate responses and host anti-viral responses, may be more challenging to discern because of variation in early viral replication and viral clearance (Neidleman et al, 2021). Thus, incorporating larger sample sizes may provide deeper insights into the effects of RBD-mAb on early immune dynamics.…”
Section: Mabs Limit Effector Cd4 T Cell Influx In Csfmentioning
confidence: 99%